Aerobic exercise attenuates insulin resistance via restoring branched chain amino acids homeostasis in obese mice - Cao, Wei; Liu, Yajin; Wei, Hao; Dong, Yunfeng; Sun, Haipeng; Zhang, Xuejiao; Qiu, Junqiang (Frontiers in Nutrition, 2024)
Emerging evidences suggests that the disrupted branched-chain amino acids (BCAAs) homeostasis and elevated BCAAs promote obesity-related insulin resistance (IR). Exercise improves insulin sensitivity. However, whether BCAAs plays a role in the exercise attenuated IR remains to be fully investigated. Methods: In this study, male C57BL/6J mice were induced to become diet induced obese (DIO) and served as subjects. The initial investigation focused on the impact of exercise on IR and BCAAs. The DIO mice were randomly assigned to either a sedentary group (CON, n=16) or an exercise group (EX, n=16). The EX group underwent a 12-week aerobic exercise regimen on a treadmill. After 12-week, plasma BCAAs and branched-chain keto acids (BCKAs) were measured by liquid chromatography-mass spectrometry, glucose tolerance test (GTT) and insulin tolerance test (ITT) were performed, and the expression of BCAAs catabolic proteins, as well as AKT T308 in gastrocnemius muscle and liver tissues, were evaluated using western blotting. Subsequently, the study explored the role of BCAAs in enhancing IR through exercise. Mice were randomly allocated into 4 groups: sedentary group (CON, n=8), sedentary with BCAAs supplementation group (CON+BCAA, n=8), exercise group (EX, n=16), and exercise with BCAAs supplementation group (EX+BCAA, n=16). After 12-week, plasma BCAAs and BCKAs, GTT and ITT tests were performed, and AKT T308, as well as p70S6K T389 in gastrocnemius muscle and liver, were compared between the EX group and the EX+BCAA group. Additionally, AMPKα T172 in both tissues was measured across all four groups. Results: 12‐week aerobic exercise improved insulin sensitivity in DIO mice, increased the catabolic capacity of BCAAs in both skeletal muscle and liver, and decreased plasma BCAAs levels. Importantly, BCAAs supplementation elevated the plasma level of BCAAs and counteracted the exercise-attenuated IR. In skeletal muscle and liver tissues, BCAAs supplementation impaired the exercise-improved insulin signaling without enhancing mTOR activity. AMPK activity was enhanced by aerobic exercise, which was abolished by BCAAs supplementation. Conclusion: Aerobic exercise attenuated insulin resistance via restoring BCAAs homeostasis and AMPK activity. The impacts of BCAAs intake on the metabolic effects of exercise sheds light on the combined exercise and nutrition intervention strategy for diabetes management.